Six-month follow-up of minimally invasive nerve-sparing complete excision of endometriosis: What about dyspareunia? - Claudio Peixoto Crispi; Claudio Peixoto Crispi; Bruna Rafaela Santos de Oliveira; Nilton de Nadai Filho; Fernando Maia Peixoto-Filho; Marlon de Freitas Fonseca (PLoS ONE, 2021)
Study objective To assess individual changes of deep dyspareunia (DDyspareunia) six months after laparoscopic nerve-sparing complete excision of endometriosis, with or without robotic assistance. Methods This preplanned interdisciplinary observational study with a retrospective analysis of intervention enrolled 126 consecutive women who underwent surgery between January 2018 and September 2019 at a private specialized center. Demographics, medical history and surgery details were recorded systematically. DDyspareunia (primary outcome), dysmenorrhea and acyclic pelvic pain were assessed on self-reported 11-point numeric rating scales both preoperatively and at six-month follow-up. Cases with poor prognosis in relation to dyspareunia were described individually in greater detail. Results Preoperative DDyspareunia showed weak correlation with dysmenorrhea (rho = .240; P = .014) and pelvic pain (rho = .260; P = .004). Although DDyspareunia improved significantly (P < .001) by 3 points or more in 75.8% (95%CI: 64.7-86.2) and disappeared totally in 59.7% of cases (95%CI:47.8-71.6), individual analysis identified different patterns of response. The probability of a preoperative moderate/severe DDyspareunia worsening more than 2 points was 4.8% (95%CI: 0.0-10.7) and the probability of a woman with no DDyspareunia developing "de novo" moderate or severe DDyspareunia was 7.7% (95%CI: 1.8-15.8) and 5.8% (95%CI: 0.0-13.0), respectively. In a qualitative analysis, several conditions were hypothesized to impact the post-operative DDyspareunia response; these included adenomyosis, mental health disorders, lack of hormone therapy after surgery, colporrhaphy, nodule excision in ENZIAN B compartment (uterosacral ligament/parametrium), the rectovaginal septum or the retrocervical region. Conclusion Endometriosis surgery provides significant improvement in DDyspareunia. However, patients should be alerted about the possibility of unsatisfactory results.